(untitled) (Research, Society and Development, 2021)
This study was undertaken to determine the incidence and potential risk factors associated with Acute Respiratory Distress Syndrome (ARDS) in pediatric oncologic patients undergoing invasive mechanical ventilation and the association between mortality risk factors and ARDS. Retrospective cohort study was conducted using data analysis of patients on admission to the PICU, that were submitted to invasive mechanical ventilation for over 24 hours. Shapiro-Wilk test and bivariate analysis within the group exposed to ARDS and the one not exposed, as well as Fisher’s, Wilks G, chi-square tests, and Poisson logistic regression were applied, with significant variables p <0.05 and 95% CI. From que 181 pediatric cancer patients included in the study, 69.06% had ARDS, with 48% leukemia, 58.4% pneumonia, 60.8% febrile neutropenia, and 76.1% were in the maintenance chemotherapy phase; pH expressed higher relation with ARDS outcome and mortality. These data are important as this is one of the first studies carried out on ARDS in the pediatric cancer population in the North of Brazil, but further research is needed to better correlate risk factors and acute respiratory distress syndrome on such population.